2015
DOI: 10.1371/journal.pone.0132492
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Retinopathy and DME in Type 2 Diabetes—Results from the German/Austrian DPV Database

Abstract: To assess the prevalence and risk factors for early and severe diabetic retinopathy and macular edema in a large cohort of patients with type 2 diabetes Retinopathy grading (any retinopathy, severe retinopathy, diabetic macular edema) and risk factors of 64784 were prospectively recorded between January 2000 and March 2013 and analyzed by Kaplan–Meier analysis and logistic regression. Retinopathy was present in 20.12% of subjects, maculopathy was found in 0.77%. HbA1c > 8%, microalbuminuria, hypertension, BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 28 publications
7
78
0
6
Order By: Relevance
“…Again, this largely reflects epidemiological findings: The Gutenberg Health Study found that, in Germany, the incidence of diabetic retinopathy (DME or milder forms) was similar in both genders, but the incidence of diabetes mellitus itself was higher among males than females [20, 21]. A higher incidence of DME in males compared to females, as seen in OCEAN, may be founded in a gender bias in the incidence of underlying diabetes.…”
Section: Discussionmentioning
confidence: 76%
“…Again, this largely reflects epidemiological findings: The Gutenberg Health Study found that, in Germany, the incidence of diabetic retinopathy (DME or milder forms) was similar in both genders, but the incidence of diabetes mellitus itself was higher among males than females [20, 21]. A higher incidence of DME in males compared to females, as seen in OCEAN, may be founded in a gender bias in the incidence of underlying diabetes.…”
Section: Discussionmentioning
confidence: 76%
“…Subjects with DME are at a higher risk for cardiovascular disease and kidney dysfunction 18 19. VIVID and VISTA trials analysed systemic risk factors of repeated intraocular aflibercept injection in 466 subjects with DME at week 100.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, bevacizumab is the most cost-effective medication for control of DME21 compared with ranibizumab (40 times less expensive) or aflibercept 18 20 22. The actual compounded cost is 60 times less for ziv-aflibercept than for aflibercept, if the 4 mL ziv-aflibercept phial is divided into 40 aliquots (4 mL Zaltrap 25 mg/mL phial costs US$536 while single Eylea phial costs US$1200 in Lebanon).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycaemia is the major pathogenetic determinant of diabetic retinopathy and most (meta-)analyses highlight disease duration and level of glycaemia (reflected by HbA 1c ) as being the most important risk factors for disease onset and progression [43][44][45][46]. However, the magnitude of their contribution to the risk of complications was put into perspective by the DCCT/Epidemiology of Diabetes Interventions (EDIC) research group, who calculated that HbA 1c only accounted for up to 11% of the entire risk for complications and concluded that most of the variation in risk was explained by factors not imaged by glycaemia [47].…”
Section: Modelling Early Diabetic Retinopathymentioning
confidence: 99%